2022
DOI: 10.3389/fphys.2022.937033
|View full text |Cite
|
Sign up to set email alerts
|

Effects of short-term heat stress on the activity of three antioxidant enzymes of predatory mite Neoseiulus barkeri (acari, phytoseiidae)

Abstract: To study the physiological mechanisms of Neoseiulus barkeri in response to short-term heat stress, the eggs and the emerged adults were exposed to 38, 40, and 42°C, 85% ± 5%RH,16 h:8 h (L:D) for 2, 4, and 6 h. The activities of superoxide dismutase (SOD), peroxidase (POD), and catalase (CAT) as well as the protein content of N. barkeri were examined. All treatments caused significant different changes compared to the untreated control. The protein content increased as the temperature increased, while it showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 58 publications
1
0
0
Order By: Relevance
“…Additionally, at the same temperature, with the extension of duration time, SOD, POD, and CAT activity and the T-AOC were changed, which suggested that various exposure times also effect SOD, POD, and CAT activity and the T-AOC. Li et al found similar results in the study on the effects of short-term heat stress on the antioxidant enzymes of N. barkeri [ 51 ].…”
Section: Discussionsupporting
confidence: 60%
“…Additionally, at the same temperature, with the extension of duration time, SOD, POD, and CAT activity and the T-AOC were changed, which suggested that various exposure times also effect SOD, POD, and CAT activity and the T-AOC. Li et al found similar results in the study on the effects of short-term heat stress on the antioxidant enzymes of N. barkeri [ 51 ].…”
Section: Discussionsupporting
confidence: 60%
“…They typically use glutathione (GSH) as an electron donor [24]. Based on our previous research, short-term heat stress resulted in increased expression of SOD, CAT, and Prx activities in N. barkeri, and the enzyme activity reached its maximum at 40 • C-4 h [25]. A notable rise in antioxidant enzyme activities suggests the presence of oxidative stress and a positive capability to counteract it by eliminating ROS from cells [26,27].…”
Section: Introductionmentioning
confidence: 99%